Evaluability Assessment: Clarifying Organizational Support and Data Availability - Joseph Hare; Timothy Guetterman (The Evaluation Center at Western Michigan University, 2014)
Evaluability assessment (EA) emerged in the 1970s as a way to ensure a program was ready for summative evaluation.  The primary purpose was assessing the presence of measureable program objectives (Trevisan, 2007), yet evaluators conducting EA encountered difficulty with unclear, ambiguous methods (Smith, 2005).  To address this concern, the purpose of this study was to clarify two aspects of EA, organizational support and data availability.  In practice, organizational stakeholders must support the evaluation project to ensure it is pursued to completion.  In addition, the availability of operational data facilitates analysis of the evaluand effect.  This qualitative study consisted of interviews with evaluators, organizational stakeholders, and technology personnel followed by thematic analysis.  The findings indicate the importance of specific organizational and data related considerations that affect evaluability. The researchers recommend considerations that elaborate upon the existing EA framework.  The recommended evaluability considerations assist evaluators in identifying ill-advised evaluations and enhancing the likelihood of success in ongoing studies.